Power profiling in elite U23 riders during a competitive season - Leo, P.; Mujika, I.; Menz, V.; Lawley, J. (Journal of Science and Cycling, 2019)
Purpose: Changes in the power profile of elite U23 cyclists throughout a competitive season could provide valuable information about racing demands and the training process. A rider`s power-duration relationship shows a dynamic behaviour affected by training and racing, and repeated computation is required to gain accurate insights into a rider`s performance capabilities. Assessing the power-duration relationship by means of different performance tests in the field is one common way to proceed. However, such tests require regular attempts as well as a motivated and rested athlete, which could be difficult during a competitive season. Therefore, the aim of this study was to investigate changes in the power-duration relationship based on peak power output values obtained during racing.